Atmospheric Warming-Associated Phenological Earliness Does Not Increase the Length of Growing Season in Himalayan Trees. Issue 6 (4th October 2021) - Negi, G C S; Singh, Pradeep; Singh, S P
Abstract: We present phenological data for two time periods (1985–1987 and 2014–2016) on major tree species ( Shorea robusta, Pinus roxburghii, Myrica esculenta, Quercus leucotrichophora, Rhododendron arboreum, Quercus floribunda, and Machilus duthiei ) occurring along an altitudinal gradient of 300–2, 200 m asl of Himalayan forests (a data-deficient region identified by the IPCC, 2007 ), and show that bud break and leafing in trees has advanced at 0.20 days/year, which is associated with a significant ( P  < 0.001) increase in atmospheric temperature (0.038°C/year) over the years in the study area. Also, the leaf drop period has advanced correspondingly (0.40 days/year); hence, the length of season (LOS) did not increase in these trees. This finding is contrary to the report of increase in LOS due to climatic warming from temperate latitudes of the world and satellite-based studies in Himalayan region. Arguably, phenomena such as bud break and leafing may not be captured by remote sensing, which is critical for determining the impact of climate change on the forest vegetation of the eco-sensitive Himalayan region. We suggest that this phenological earliness may alter forest structure and functioning and associated ecosystem services of these forests in the long run.